1997
DOI: 10.1007/pl00004938
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adrenoceptor and muscarinic receptor blockade on the cardiovascular effects of exogenous noradrenaline and of endogenous noradrenaline released by infused tyramine

Abstract: This study aimed firstly to compare the in vivo cardiovascular effects of exogenously administered and of endogenously released noradrenaline; secondly to characterize the adrenoceptors mediating these responses; thirdly to assess the influence of parasympathetic tone on the cardiovascular effects of noradrenaline. In two randomised placebo-controlled studies, healthy, young, male volunteers received intravenous (i.v.) infusions of noradrenaline at six incremental doses of 10-160 ng/kg/min and-in order to rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
3
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 41 publications
5
43
3
1
Order By: Relevance
“…Schafers et al showed that the stimulation of β1-adrenergic receptors induces the inotropic and chronotropic effects of norepinephrine. 21 Similar results were reported by McDavitt, who emphasized that the ability of β1-adrenergic receptor signaling to initiate arrhythmia is illustrated by exercise-induced tachyarrhythmias caused by norepinephrine release from sympathetic nerve ending. 22 Taken together, these results and our results suggest that bisoprolol has greater ability to suppress HR of patients with HF than carvedilol, as the former is a highly selective β1-adrenergic receptor blocker.…”
Section: Effects Of Carvedilol Vs Bisoprolol In Chfsupporting
confidence: 79%
“…Schafers et al showed that the stimulation of β1-adrenergic receptors induces the inotropic and chronotropic effects of norepinephrine. 21 Similar results were reported by McDavitt, who emphasized that the ability of β1-adrenergic receptor signaling to initiate arrhythmia is illustrated by exercise-induced tachyarrhythmias caused by norepinephrine release from sympathetic nerve ending. 22 Taken together, these results and our results suggest that bisoprolol has greater ability to suppress HR of patients with HF than carvedilol, as the former is a highly selective β1-adrenergic receptor blocker.…”
Section: Effects Of Carvedilol Vs Bisoprolol In Chfsupporting
confidence: 79%
“…Our results with tyramine are at variance with Schäfers et al, 11 who reported a reduction in DBP and an increase in SBP and cardiac inotropic performance in healthy males and concluded that the effects of intravenous tyramine are mainly mediated by Figure 1 Effect of intravenous noradrenaline (a) and tyramine (b) given alone or in the presence of propranolol at equivalent noradrenaline plasma concentrations. Percent changes from baseline mean arterial blood pressure, pulse rate and total electromechanical systole QS2c in males (n ¼ 10, hatched columns) and females (n ¼ 9, open columns) are presented as means 7 s.e.m.…”
contrasting
confidence: 58%
“…Heart rate (HR) (bpm) was calculated from the RRinterval of the electrocardiogram, which was recorded using a Siemens-Cardirex s multichannel ink jet recorder (Siemens Medizintechnik, Erlangen, Germany) as previously described. 29,30 We used impedance cardiography to measure central haemodynamics. Impedance cardiography agrees closely with measurements obtained by Doppler echocardiography or thermodilution, 31 and is acceptable for clinical use particularly in studies investigating young subjects free from any cardiovascular disease.…”
Section: Anthropometric and Haemodynamic Parametersmentioning
confidence: 99%